Adherence to Mediterranean Style Dietary Pattern and Total Cancer Risk in the Framingham Offspring Cohort Study (P05-040-19). (13th June 2019) - Yiannakou, Ioanna; Singer, Martha; Jacques, Paul; Moore, Lynn
Abstract: Objectives: This study examines the prospective association between adherence to a Mediterranean style dietary pattern and cancer risk among men and women in the Framingham Offspring (FOS) cohort. Methods: The Mediterranean style dietary pattern (MSDP) score was derived from a semi-quantitative food frequency questionnaire taken at examination visit 5 in the prospective FOS cohort. Subjects included 3199 participants (1703 women and 1496 men), aged 30 years old and older, who were free of prevalent cancer. The MSDP score was classified into tertiles and also dichotomized (MSDP score <22 vs. ≥22) used to evaluate the association between the MSDP and cancer risk through the ninth examination cycle. Cox proportional-hazard models were used to estimate hazard ratios (HRs) and 95% confidence intervals (CIs) adjusting for confounding by age, physical activity, body mass Index, and pack-years of cigarette smoking. Factors found not to confound the effects of the MSDP were excluded from final models. Results: During a mean follow-up of approximately 11.5 years, 377 and 273 cancer cases were documented among men and women, respectively. Women in the upper two tertiles of the MSDP score had a 25–30% lower cancer risks than women in the lowest tertile [(HR: 0.70, 95% CI:0.52–0.96 (tertile 2); HR, 0.75; 95% CI:0.56–1.00 (tertile 3)]. Effects in men were weaker [HR: 0.94, 95% CI:0.74–1.21 (tertile 2); HR, 0.90; 95% CI:0.68–1.17(tertile 3)]. The protective effects of higher MSDP adherence were stronger among non-smokers and former smokers than among current smokers. Compared with current smokers with a MSDP score < 22, non-smokers and former smokers with higher MSDP scores had approximately 43% and 39% reductions in total cancer risk, respectively (HR: 0.57; 95% CI: 0.43–0.75 for non-smokers with high MSDP; HR: 0.61; 95% CI: 0.47–0.79 for former smokers with high MSDP scores).SDP scores). Conclusions: In this large cohort study, higher adherence to MSDP was associated with reduced risk of total cancer, especially among women. Beneficial effects of the MSDP were also stronger among non-smokers and former smokers. Funding Sources: N/A.